2017
DOI: 10.4000/jso.7696
|View full text |Cite
|
Sign up to set email alerts
|

Migrants vers la ville communautés translocales et le mythe du retour au Vanuatu : le cas de Paama

Abstract: Urbanization in Vanuatu has increased rapidly in recent decades. Circular mobility has gradually given way to urban permanence as second and third generations grow up in urban centres. Migrants from the small outer island of Paama are numerically signiicant in the capital Port Vila with more Paamese living there than in their 'home' island. Few have returned to Paama, despite a substantial proportion of all generations professing intentions to do so, 'one day', after other goals had been realised, while mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…We also explored the direction of the inferred migrations, and found that both female and male migrations mainly occurred from the northernmost and southernmost islands towards the center of the archipelago (Fig. 3 C ), where Port Vila – the largest city – has developed (37).…”
Section: Resultsmentioning
confidence: 99%
“…We also explored the direction of the inferred migrations, and found that both female and male migrations mainly occurred from the northernmost and southernmost islands towards the center of the archipelago (Fig. 3 C ), where Port Vila – the largest city – has developed (37).…”
Section: Resultsmentioning
confidence: 99%
“…While the diversity of migration possibilities has increased, the legal rights and entitlements of Pacific island migrants have tended to decline -including the right to stay -exemplifying a new stratification and inequality within migration. Foreign migrants are all too likely to be seen as foreign workers on temporary visas, easily able to be replaced and removed and denied citizenship and residential status: a new precarity (Underhill and Rimmer, 2015;Petrou and Connell, 2017). Temporary agricultural workers are denied permanency but encouraged to return every year, in order to take advantage of their acquired skills, becoming "permanently temporary" and constantly floating, a situation that does nothing for equity, challenges the etymology of "guest" workers and may enhance domestic problems.…”
Section: Discussionmentioning
confidence: 99%
“…Towns and cities have grown rapidly in the years since independence, and most urban residents are in Melanesian cities and towns. Urban birth rates are high, and a growing proportion of urban residents are now of a second or higher generation with few ties to "home" areas and limited ability and will to return (Petrou and Connell, 2017). Population densities are highest in capital cities despite the active discouragement of urban migration and residence.…”
Section: Rural-urban Migration and Urbanisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is different for internal migration. Younger people in particular migrate to the economic centers of the country, as these places offer, for example, more diverse educational or employment opportunities than the islands of Torba (Petrou and Connell, 2017). There is a more or less regular exchange of money and goods such as clothing, technical appliances or food between the people who have left and the families who have stayed behind.…”
Section: Efficient Resource Allocationmentioning
confidence: 99%